IN VITRO STUDIES ON ADHESION AND THE EFFECT OF CYTOTOXICITY OF BIFIDOBACTERIUM SPP. USING CELL LINES - Subhashini, S.; Lavanya, J.; Meignanalakshmi, S. (European Scientific Journal, ESJ, 2013)
The objective of this study was to elucidate adhesion property and the effect of cytotoxicity studies of Bifibobacterium in vitro. Bifidobacterium strains were isolated from milk and milk products, around twelve strains were isolated in which four strains were identified they are- Bifidobacterium lactis, Bifidobacterium longum, Bifidobacterium bifidum and Bifidobacterium infantis. The identification was done by morphological features and biochemical tests. The isolated strains were then assayed for the adherence and antitumor activities. The Bacteria showed good adherence pattern on the HT-29 cell lines and exhibited profound inhibitory activity on cancer cell lines (Human adeno -carcinoma cell lines).